Development of High Quality Printing Paper Using Kenaf (Hibiscus Cannabinus) Fibers - Ashori, Alireza (2004)
Kenaf (Hibiscus cannabinus) is an annual non-wood plant which has shown great potential as an alternative source of papermaking fiber. The purpose of this research was to investigate the suitability of Malaysian cultivated kenaf fibers in the production of high quality printing paper. The first part of the research characterized the chemical, morphological and pulping properties of kenaf fractions. The bast fibers had a lower lignin content, higher cellulose content, and lower hemicellulose content compared to the core fibers. The whole stem kenaf had lower lignin and cellulose content, and hemicellulose and ash content was comparable to softwood. Fiber morphology results showed that kenaf bast fibers were long and slender, while the core fibers were much shorter and wider. Morphology and chemical analysis indicated that bast and core fibers were significantly different. In this part, the pulping properties of different fractions of kenaf were also studied. The pulping experiments led to the conclusion that bast fibers are relatively easy to delignify during pulping, followed by the whole stem and the core kenaf fractions. An unbleached whole kenaf pulp with high viscosity, good bleaching characteristics and relatively good yield could be produced with the kraft pulping process. The second part of the research investigated the production of bleached pulp using environmentally-friendly method, TCF. Conventional Elemental Chlorine Free (ECF) bleaching sequences were also used to compare the results with the TCF sequences. The results indicated that in contrast to unbleached kraft wood pulps, kraft kenaf pulps can be easily bleached to a brightness of 91.4% using a 4-stage TCF [Q1(PO)Q2P] bleaching sequence. This will be a significant advantage for kenaf over wood. The third part of the research studied the polymer deposition, surface topography and printability. The utilization of chitosan in sizing improved the paper strength and surface properties significantly, but its effectiveness was strongly dependent on the method of addition and concentration. Spray deposition application gave superior strength properties followed by equilibrium adsorption. It is less effective under alkaline conditions. The effect of chitosan was compared with cationic starch and polyvinyl alcohol (PVA). Sizing quality of cationic starch fairly matched with the sizing quality of chitosan, however, it was able to reduce the water absorption potential of paper more than chitosan at a same concentration (i.e. 2%). The final part of study demonstrated that the use of chitosan in optimum dosage could improve the printability and print quality of kenaf paper in terms of surface roughness, water and oil absorption, ink penetration, print density, ink set-off and gloss contrast for offset printing. The overall conclusion is that whole stem kenaf is an attractive raw material that is suitable for use in the production of high quality printing paper in areas where forest resources are inadequate to supply a kraft mill of economic size. Chitosan is recommended as an additive in conventional surface sizing to enhance strength and surface properties for printing paper.